2005
DOI: 10.1103/physreva.71.023407
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton ionization ofHeby using intense high-order harmonics in the soft-x-ray region

Abstract: We report on the multiphoton ionization processes in the soft-x-ray region ͑ഛ30 nm͒. On the basis of the measured time-of-flight spectra for both ions and electrons obtained using intense soft-x-ray pulses produced by high-order harmonics, the cross sections of the two-photon double ionization and above-threshold ionization of He are estimated. The high-intensity soft-x-ray radiation achieved by phase-matched high-order harmonics enables the investigation of these nonlinear optical processes, which were beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
121
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 28 publications
7
121
0
Order By: Relevance
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 73%
“…The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
mentioning
confidence: 99%
“…Kobayashi et al [25] were the first to observe this process and used it for an autocorrelation measurement of high-order harmonic pulses, and Moshammer et al [26] recently used it for an autocorrelation measurement of the EUV FEL pulses provided by the SPring-8 Compact SASE Source (SCSS) test accelerator [8]. The absolute two-photon ionization cross sections of He were measured using an intense high harmonic source [27] as well as the SCSS test accelerator [28]. Hishikawa et al [29] recently investigated two-and three-photon ionization of He at the SCSS test accelerator by photoelectron spectroscopy using a magnetic bottle spectrometer.…”
mentioning
confidence: 99%
“…Thanks to the high intensity of an APT, we successfully observed novel phenomena of a matter interacting nonlinearly with the APT field [21,22,24,25], and then we utilized these phenomena for showing directly the temporal shape of the APT in autocorrelation (AC) measurements [21,[26][27][28][29][30]. Nevertheless, there were two practical issues in these studies, one of which is the long data-acquisition time required for the measurements.…”
mentioning
confidence: 99%
“…In fact, the pulse energy and intensity of the APT or one harmonic pulse now reached more than µJ [19,20] and 10 12 -10 14 W/cm 2 [21,22], respectively, on the basis of the energy scaling criteria of HOH generation under the phase matching condition [23].…”
mentioning
confidence: 99%